Enhancing caregivers’ knowledge through targeted health promotion: A study at TPA Adzkia Padang - Annisa Lidra Maribeth; Ghaniyyatul Khudri; Rialta Hamda; Kurnia Maidarmi Handayani; Widia Sari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This study aimed to evaluate the effectiveness of health promotion activities for caregivers at the childcare center (TPA) Adzkia Padang. Health promotion sessions on PHBS (Clean and Healthy Living Behavior) and several health conditions including Chickenpox, Measles, Miliaria, and Diaper Dermatitis (CACAMINDER) were conducted. Participant knowledge levels were assessed using a questionnaire administered both before (pre-test) and after (post-test) the educational intervention. The distribution of knowledge levels and the scores from the pre-test and post-test were analyzed. Pre-test results indicated that 60% of participants had good knowledge, 40% had sufficient knowledge, and none had poor knowledge. Post-test results showed improvement, with 80% of participants demonstrating good knowledge and 20% having sufficient knowledge. No participants scored in the poor knowledge category. The maximum score increased from 11 to 12, while the minimum score remained constant at 8. The mean score also increased from 9 to 10. In conclusion, the health promotion activities significantly enhanced caregivers' knowledge of PHBS and various health conditions, as evidenced by improved post-test scores. These findings emphasize the importance of ongoing health education to empower caregivers with the knowledge necessary to promote and maintain toddler health.